Study of sound absorption using acoustic impedance tube - Lin, Louis Yixiang. (2009)
This report presents an experimental study on sound absorption of perforated plates by using an acoustic impedance tube. The sound absorption characteristics of thin circular plates with micro perforations are studied in a frequency range between the 50 Hz and 1600 Hz. The micro perforated plates are backed by an air cavity with various volumes adjusted in the experiment. A detail study of micro-perforated plate absorber theory based on the Helmholtz resonator principle has been reviewed and a formula in the published paper has been used to calculate the acoustic impedance of the test plates. The calculated results for the perforated plated are compared with the measured data in the present study, and good agreement between them has been observed. It is also found that micro-perforated plates backed with an air cavity make better sound absorbers than that without the cavities, and micro-perforated absorbers with smaller perforations have better sound absorption properties. Discussions of the theoretical and experimental results, details drawing of the specimen plates, experimental apparatus and procedures are presented in this report.